PENGARUH PROMOSI KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP SISWA DALAM MENCEGAH INFEKSI HIV/AIDS DI SMK NAMIRA ISLAMIC SCHOOL MEDAN - Pittauli, Nova; Sinulingga, Diana; Ariescha, Putri Ayu Yessy (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2019)
The most dangerous Human Immunodeficiency Virus / Acquired Immunodeficiency Syndrome (HIV / AIDS) in the Asia Pacific ranks second in the world at 4.8 million, deaths from AIDS amounting to 250,000 and Indonesia reaches 2% of total deaths (WHO, 2014). This study aims to analyze the effect of health promotion on students' knowledge and attitudes in preventing HIV / AIDS infection.This type of research is a pre quasi experiment. The design used was a pre-test and post-test to determine whether there was a change or not after being given treatment (intervention) to the respondent with the Wilcoxon Test Test statistical test. Population of all class X, XI Namira Islamic School field as many as 80 people.The results of this study that there is influence there is influence before (pre) and after (post) health promotion on knowledge (p